Zagotavljanje kakovosti georeferenciranja podatkov aerolaserskega skeniranja za upravljanje voda - Bric, Vasja (Geodetski vestnik, 2013)
This paper deals with the problems of quality assurance for airborne laser-scanning data. Partial results of the project entitled "Laser Scanning and Aerial Photographing of Slovenia 2011" are presented, and the quality control procedure is described. The focus is on the quality assurance of the geo-referencing used for water resource management. Important issues with an impact on the quality of data are addressed and evaluated. The quality of direct geo-referencing was investigated, and some experiences gained in the quality control of the project results are presented. The quality of the transformation of data into the national horizontal and height reference systems is also discussed. Some recommendations for the quality improvement of airborne laser-scanning data are given. This will be possible with the realisation of the new national height reference system and with the creation of the new geoid model.
Keywords: aerolasersko skeniranje; airborne laser scanning; data quality; georeferencing; georeferenciranje; kakovost podatkov; lidar; upravljanje voda; water resource management